LITERATURE REVIEW : ALTERNATIF PENCEGAHAN HIPERTENSI DALAM KEHAMILAN MENGGUNAKAN TANAMAN KELOR - Dian Juni Ekasari; Dina Mulyana Syafitri (Universitas Batam, 2026)
Hypertension in pregnancy, especially preeclampsia and eclampsia, remains a major cause of maternal and infant morbidity and mortality, and the Moringa oleifera plant with its important nutritional content can be an effective and safe alternative to lower blood pressure in pregnant women, in line with government policies in promoting the use of family medicinal plants (TOGA) in Indonesia. The purpose of this study was to analyze the Moringa Plant as an Alternative for Preventing Hypertension in Pregnancy (Preeclampsia/Eclampsia). This research method used a systematic search to identify relevant articles from 2019-2024 through journals, articles, and Web of Science, as well as additional publications from Google Scholar by searching the reference list and snowball method. The results of the study showed that the Moringa plant (Moringa oleifera) was proven effective as an alternative for preventing hypertension, including in pregnancies at risk of preeclampsia or eclampsia, with the ability to lower blood pressure and anxiety thanks to its flavonoid and antioxidant content. In addition, counseling on the benefits of Moringa leaf tea can increase public knowledge, making it a safe non-pharmacological solution for managing hypertension and potentially supporting the development of herbal product-based businesses. Keywords : Moringa, Hypertension, Pregnancy, Preeclampsia, Eclampsia